(untitled) (International conference on multidisciplinary science, 2025)
The digital economy utilizes technology in transforming industries such that automation, web transactions, and remotely delivered services become a reality. The digital economy is also responsible for a lot in terms of efficiency, new breakthroughs, and access to a larger pool of medical care and education. On its downsize, its failures in terms of a digital divide, cybersecurity, and regulating its use become a problem. As such, its speedy adoptions require governments and companies to make investments in robust infrastructure, awareness, and equitable policies. With such a transformation, society will have a chance to enjoy fruits of growth in a fuller form in an inclusive, secure, and a digital society.